Problems of investment climate assessment in an age of informationa glut - Bandarenka, Natallia; Tsimashenka, Irina (Management and Administration Journal, 2020)
The article presents a comparative assessment methodology of the investment climate (country, region, city, etc.). Unlike current approaches and methods for investment climate assessing the authors take into account not only the investment attractiveness which is formed on the basis of investment potential and investment risk, but also the investment activity. The research purpose is to calculate integral comparable indicators for the EAEU members taking quantitative data and expert assessments as a base. As a result of the research a rating of the EAEU country’s investment attractiveness was compiled. The analysis carried out by the authors showed that the Republic of Belarus in comparison with their main trading partners (Russia and Kazakhstan) has rather low production, innovation and natural resource potentials, as well as high economic and political risks. The results of the study allow identifying barriers restraining the inflow of foreign investment in the Republic of Belarus. The baseline data are statistical information published by the statistical committees of the member countries of the Eurasian Economic Union, as well as media materials, analytical reviews of research centres.